2021
DOI: 10.1161/hypertensionaha.121.17049
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Crossing Renin-Angiotensin Drugs and Cognition in the Elderly: A Meta-Analysis

Abstract: Hypertension is an established risk factor for cognitive decline and dementia in older adults, highlighting the potential importance of antihypertensive treatments in prevention efforts. Work surrounding antihypertensive treatments has suggested possible salutary effects on cognition and neuropathology. Several studies have specifically highlighted renin-angiotensin system drugs, including AT1-receptor blockers and angiotensin-converting-enzyme inhibitors, as potentially benefiting cognition in later life. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 95 publications
2
36
0
Order By: Relevance
“…Moreover, some experimental studies on the effects of telmisartan and candesartan, which are typical ARBs known to penetrate the BBB, showed an improvement in dopaminergic and mitochondrial functions in an animal PD model (Sekar et al, 2018;Ray et al, 2021). Previous clinical studies on dementia also showed that BBB-crossing RAS inhibitors have better neuroprotective effects than non-BBB-crossing agents (Ho et al, 2021;Ouk et al, 2021). Thus, our real-world evidence suggests the potential value of BBB-crossing ARBs as a prophylactic or disease-modifying therapy for PD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some experimental studies on the effects of telmisartan and candesartan, which are typical ARBs known to penetrate the BBB, showed an improvement in dopaminergic and mitochondrial functions in an animal PD model (Sekar et al, 2018;Ray et al, 2021). Previous clinical studies on dementia also showed that BBB-crossing RAS inhibitors have better neuroprotective effects than non-BBB-crossing agents (Ho et al, 2021;Ouk et al, 2021). Thus, our real-world evidence suggests the potential value of BBB-crossing ARBs as a prophylactic or disease-modifying therapy for PD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial of losartan, a classical AGTR1-receptor blocker, did not reduce rates of brain atrophy or cognitive decline compared to placebo in patients with mild-moderate AD ( 13 ). In view of recent studies indicating that BBB penetrating RAS agents better preserve memory compared to nonpenetrant BBB ( 48 , 49 ), future clinical trials should focus on RAS modifiers known to cross the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…lood pressure (BP) and its modulation by antihypertensive treatment has been extensively investigated in relation to cognitive decline and dementia. [1][2][3][4][5][6][7] The role of BP elevation in dementia risk has garnered substantial attention in part because of the clinical availability of BP measures, the high rates of hypertension in older adults, and the wide availability of antihypertensive medications. [8][9][10] Recent randomized controlled trial results from the SPRINT study (Systolic Blood Pressure Intervention Trial) indicate aggressive BP lowering prevents cognitive impairment, relative to standard BP control, 11 underscoring the potential importance of BP and its modulation in the prevention of cognitive decline.…”
mentioning
confidence: 99%